Lightweight Semantic Mesh Mapping for Autonomous Vehicles - Herb, Markus; Weiherer, Tobias; Navab, Nassir; Tombari, Federico (Proceedings - IEEE International Conference on Robotics and Automation, 2021)
Lightweight and semantically meaningful environment maps are crucial for many applications in robotics and autonomous driving to facilitate higher-level tasks such as navigation and planning. In this paper we present a novel approach to incrementally build a meaningful and lightweight semantic map directly as a 3D mesh from a monocular or stereo sequence. Our system leverages existing feature-based visual odometry paired with learned depth prediction and semantic image segmentation to identify and reconstruct semantically relevant environment structure. We introduce a probabilistic fusion scheme to incrementally refine and extend a 3D mesh with semantic labels for each face without intermediate voxel-based fusion. To demonstrate its effectiveness, we evaluate our system in outdoor driving scenarios with monocular depth prediction and stereo and present quantitative and qualitative reconstruction results with comparison to ground truth. Our results show that the proposed approach achieves reconstruction quality comparable to current state-of-the-art voxel-based methods while being much more lightweight both in storage and computation.
CRIS-Team Scopus Importer:2023-03-08